Optimization of a chimney design for cooling efficiency of a radial heat sink in a LED downlight. (15th April 2016) - Park, Seung-Jae; Jang, Daeseok; Yook, Se-Jin; Lee, Kwan-Soo
Highlights: A cooling system that consists of a chimney and a radial heat sink is developed. A chimney set-up improves the cooling efficiency of a heat sink and reduces the mass of a structure. The design of a chimney is optimized with considering the cooling efficiency and the mass. Abstract: A cooling system, consisting of a chimney and a radial heat sink, was developed for a light-emitting diode (LED) downlight to replace a conventional light for saving energy. Natural convection was simulated with a numerical model that was verified experimentally. When the chimney was installed around the radial heat sink, the cooling efficiency of the heat sink was improved because the cooling air was able to move to the center of the heat sink. Furthermore, the mass of the surrounding structure could be reduced due to the superior geometric characteristics of the chimney versus a hollow cylinder. The effects of the fin-type of the radial heat sink and the thermal conductivity of the chimney were analyzed. A parametric study of the geometric factors of the chimney was conducted and a multidisciplinary design optimization, which considered the chimney mass and cooling efficiency of the heat sink, was carried out. Consequently, installing the chimney can improve the heat sink's cooling efficiency by up to 20% (while maintaining the mass of the surrounding structure) or reduce the mass of the surrounding structure by up to 60% (for a given cooling efficiency), as compared to the installation of the hollow cylinder.